Participatory processes towards food sovereignty and good living in Cerro Negro del Tirao, Salta, Argentina - Di Fonzo, Rodolfo (2023)
Large areas of the Argentine Northwest region are still inhabited by family farmers. Despite the de-structuring and de-peasantization processes of rural farming spaces, they are the ones who produce the food that is socially and culturally consumed in the region. In this paper we propose to reflect on different actions jointly conducted by a rural community in the province of Salta, Argentina, and an action-research group from the Non-Conventional Energy Research Institute (INENCO), which seeks to contribute to food sovereignty and good living. At the same time, we seek to characterize a region that would be unknown in the academic field such as the hills of Salta.